Automating Multi-Cloud Infrastructure: Leveraging Terraform and IaC for Scalable, Secure, and Efficient Cloud Management - Perumalsamy Ravindran, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Cloud computing transformation has revolutionized digital infrastructure management, particularly in multi-cloud environments. The substantial growth in cloud adoption, especially in Infrastructure as a Service, reflects increasing confidence in cloud-based solutions across industries. Implementing Infrastructure as Code principles, robust security frameworks, and automated compliance mechanisms enables organizations to achieve enhanced operational efficiency and reduced deployment times. The effectiveness of cloud-native technologies and automated infrastructure management becomes evident through comprehensive case studies spanning financial institutions and technology startups. The integration of sophisticated deployment models, particularly in the banking and financial services sector, demonstrates the maturity of cloud solutions in handling sensitive operations. The emergence of Terraform as a leading Infrastructure as Code tool, supported by its provider-agnostic architecture and effective state management capabilities, further validates the evolution of infrastructure automation practices.
Keywords: Cloud Computing; Infrastructure as Code; Multi-cloud Architecture; Security Automation; DevOps Integration